Scanning electron microscopy characterization of structural features in suspended and non-suspended graphene by customized CVD growth - Lee, Jaesung; Zheng, Xuqian; Roberts, Robert C.; Feng, Philip X.-L. (Diamond and related materials, 2015)
We report an improved recipe for synthesizing high quality graphene through chemical vapor deposition (CVD), scanning electron microscopy (SEM) characterization of CVD graphene, and optimized SEM imaging conditions for efficient visualization of surface features in CVD graphene. We have developed an optimized graphene growth recipe by characterizing the quality of as-grown graphene using Raman spectroscopy and SEM. We have examined graphene samples both on copper (Cu) and silicon dioxide (SiO2) substrate using SEM. We have found that features on the samples are highly sensitive to both SEM imaging conditions and the type of detector used. With low acceleration voltage (1keV), immersion lenses, and through the lens detector, we have clearly observed fine features including wrinkles, folding lines, defects, and different layer numbers of graphene, many of which are not visible in un-optimized SEM images. Further, we demonstrate mechanical bulging of suspended CVD graphene membranes covering microtrenches by using electron beam to activate the trapped gas underneath. Our findings and techniques can lead to improved characterization, understanding, and manipulation of graphene and other two-dimensional materials. •Exploration of optimized CVD graphene growth recipe and Raman characterization.•Systematic investigations of CVD graphene surface features using SEM.•Optimizing SEM imaging conditions for CVD graphene on Cu and SiO2 substrates.•Releasing and bulging of wet-transferred graphene membranes by electron beam irradiation.